Association of baseline HBcAg and HBV DNA with persistent detectability of HBV RNA during NA therapy - Lanjie Wu; Zixiang Pan; Jianli Yu; Xitan Yue; Fang He; Lili Yu; Ling Pan; Yuyan Wu; Chuntao Zhou; Peiye Yan; Hongying Pan (PLoS ONE, 2026)
Objective Even after long-term nucleos(t)ide analogue (NA) therapy achieves hepatitis B virus (HBV) DNA suppression in patients with chronic hepatitis B (CHB), serum HBV RNA may remain detectable. HBV RNA reflects intrahepatic viral transcriptional activity. This study identified baseline traits and predictors of persistent HBV RNA positivity during NA therapy after sustained HBV DNA suppression. Methods This retrospective study included 155 CHB patients who underwent liver biopsy before initiating NA therapy, subsequently achieved sustained HBV DNA suppression on continuous NA therapy. Patients were classified into two groups according to HBV RNA status during therapy. Baseline clinical, virological and histological variables were assessed by multivariate logistic regression. Correlations between HBV RNA and serological markers were also assessed. The diagnostic performance of the model was analyzed using area under the receiver operating characteristic (AUC) and boostrap internal validation. Results Overall, 47.7% achieved undetectable serum HBV RNA. Higher baseline HBV DNA and absence of intrahepatic hepatitis B core antigen (HBcAg) independently predicted persistent HBV RNA positivity (both P < 0.001). The combined assessment of HBcAg with HBV DNA improved predictive accuracy (AUC = 0.780), outperforming either marker alone. The AUC value of bootstrap internal validation was 0.756. Across the cohort, HBV RNA showed moderate correlation with hepatitis B surface antigen (HBsAg), hepatitis B e antigen (HBeAg) and hepatitis B e antibody (HBeAb). Correlations were minimal in HBeAg-negative patients and most evident in HBeAg-positive patients. Conclusion Incorporating HBcAg histology with baseline HBV DNA may enable more individualized treatment strategies during antiviral therapy. Correlations between HBV RNA and traditional markers are primarily observed in HBeAg-positive patients.